Internationally qualified nurses' perspectives on transitioning specialty skills within Australia: A content analysis - Chanchal Kurup; Adam Scott Burston; Vasiliki Betihavas; Elisabeth Ruth Jacob (Wiley, 2024)
Abstract Aim To explore internationally qualified nurses' perceptions regarding the facilitators and barriers to specialty skill transfer in Australia. Design The study utilised a descriptive research design with a cross‐sectional survey. Data were collected from July to September 2022. Methods A self‐designed survey was distributed through social media, snowballing and nursing professional organisations. The survey included six open‐ended questions which were analysed using thematic content analysis. Results Sixty‐three participants completed the open‐ended questions in the survey. The findings identified a range of facilitators (support, previous experience, self‐agency) and barriers (systems barriers, bias/discrimination, being undervalued, lack of trust) to skill transition. Conclusion Recognising and addressing facilitators and barriers, coupled with creating customised pathways for specialty skill integration, are essential for optimising the utilisation of specialised skills in internationally qualified nurses. Impact This study aims to explore the barriers and facilitators involved in maximising skill utilisation among internationally qualified nurses in Australia. Identifying these barriers and facilitators is essential for improving patient care, as it will guide the development of strategies for safe nursing service delivery and the optimisation of skill usage. These findings hold significant implications for policymakers, healthcare organisations and nurses, providing valuable insights into how to address these obstacles and capitalise on the factors that make skill transfer smoother and more effective. Patient or Public Contribution Sixty‐three internationally qualified nurses shared their experiences and opinions.